EFFECTS OF CONFLICT BETWEEN CROP AND LIVESTOCK FARMERS ON AGRICULTURAL PRODUCTION IN NORTHERN PLATEAU STATE, NIGERIA - Rinlat A. S.; Haruna U.; Yakubu, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the effect of conflicts between crop and livestock farmers on agricultural production in the Northern Plateau State. A multistage sampling technique was used to select 81 crop and 55 livestock farmers for the research. Primary data were collected using a structured questionnaire. Data were analysed using both descriptive and inferential statistics. The results for the study showed that the majority (66.13%) of both crop and livestock farmers were male and above 50 years old. It also revealed that both crop and livestock farmers appeared to be formally educated (33.87%). More so, farm size, output, and the herd size of farmers before and after the conflict were all compared. The result showed that they were significantly different at p<0. 001. It therefore revealed that conflict has a positive effect on farm size, output and herd size of farmers. The major constraints to conflict resolution include the use of law enforcement structures with mean scores of (5.87, 6.11), a lack of punishing conflict perpetrators (4.90, 5.58), weak policies (4.58) and a poor implementation of policies by the government (5.58). The study concluded that conflict had a positive effect on agricultural production (farm size, output, and herd size of farmers). The study recommended that dialogue, instead of the use of law enforcement structures, ranching, educating crop and livestock farmers, punishing perpetrators of conflict and full implementation of policies by the government, among others, will go a long way in resolving conflict in the study area.